Clinical and laboratory features of patients with focal lymphocytic sialadenitis on minor salivary gland biopsy for sicca symptoms: A single-center experience. Issue 13 (2nd April 2021) - Ayesha, Bibi; Fernandez-Ruiz, Ruth; Shrock, Devin; Snyder, Brittney M.; Lieberman, Scott M.; Tuetken, Rebecca; Field, Elizabeth; Singh, Namrata
Abstract : Abstract: Minor salivary gland biopsy (MSGB) is often used in patients lacking specific autoantibodies (seronegative patients) to confirm the presence of focal lymphocytic sialadenitis (FLS), which would suggest a diagnosis of Sjogren syndrome. There are no current guidelines indicating when to refer patients for MSGB. The objective of our study was to ascertain distinguishing clinical and laboratory features among individuals with sicca symptoms based on their serologic and histopathologic status, and to identify factors associated with FLS. Using a cross-sectional study design, patients ages 18 years or older with sicca symptoms who had MSGB performed at the University of Iowa from January 2000 to December 2016 were selected for chart reviews. The clinical and laboratory features of patients with and without FLS were analyzed using exact univariate and multivariable logistic regression, with Bonferroni correction for multiple comparisons. We identified 177 patients who had MSGB performed and available clinical data. A total of 133 patients had FLS, 37 (27.8%) were seropositive (positive-anti-Sjogren syndrome type A [SSA] and/or anti-Sjogren syndrome type B) and 96 (72.2%) were seronegative. Dry eyes (unadjusted odds ratio [OR]: 5.17, 95% confidence interval [CI]: 1.16–26.30; adjusted odds ratio [aOR]: 12.58, 95% CI: 1.70–167.77) and the presence of anti-SSA (OR: 7.16, 95% CI: 1.70–64.24; aOR: 8.82, 95% CI: 1.73–93.93) were associated with FLS. Smoking (aOR 0.27, 95% CI: 0.11–0.63) and antihistamine use (aOR 0.23, 95% CI: 0.08–0.63) were associated with lower odds of FLS. Our study suggests that dry eyes and anti-SSA positivity are associated with FLS. Smoking and antihistamine use were associated with lower odds of FLS. In the appropriate clinical context, seronegative patients with sicca symptoms and no smoking history could be considered for MSGB. A thorough medication and smoking history should be performed in all patients before referral for MSGB.